Influence of Megasphaera elsdenii and feeding strategies on feedlot performance, compositional growth, and carcass parameters of early weaned, beef calves - DeClerck, Jonathan C (Transl Anim Sci, 2020)
Simmental–Angus calves [n = 135; 72 steers and 63 heifers; body weight (BW) = 212.4 kg ± 36.1] were early weaned (~5 mo) to evaluate multiple feeding regimens (conventional vs. aggressive energy diets ± Megasphaera elsdenii NCIMB 41125 (M. elsdenii culture (MEC); Lactipro Advance; MS Biotec Inc., Wamego, KS) in order to elucidate the optimal development strategy. Objectives were measured by tracking the effects of caloric density and oral drenching of growing phase performance and subsequent carcass traits. The 72-d experiment featured three groups: 1) control (CON), fed exclusively a 35% roughage diet; 2) aggressive (AGR), fed a blend of a 10% and 35% roughage diets; 3) MEC, fed the same diet as AGR and drenched with 50 mL of M. elsdenii NCIMB 41125 on day 1. A subset of calves (n = 45) was equipped with wireless rumination tags (Allflex Flex Tag; SCR Engineers, Ltd; Netanya, Israel), which logged daily rumination and general activity. Skeletal growth variables were assessed by measuring wither and hip height pretrial and posttrial. Ultrasonography provided additional resolution concerning growing phase compositional gain, which was later verified by carcass data collection. Data were analyzed as a nested analysis of variance with BW and gender serving as blocking factors. The increased caloric density of the diets administered to MEC and AGR calves resulted in greater average daily gain and gain:feed values compared with CON even during the first 21 d of diet acclimation (P ≤ 0.05). Additional fiber concentration of CON diets led to increased rumination times in 9 of the 10 wk of trial (P ≤ 0.10). No differences amongst treatments were detected for skeletal variables or ultrasound 12th rib fat. Cattle fed CON diets posted 3.4% inferior BW at the end of the growing period trial and a 3.8% reduction in hot carcass weight (HCW), reinforcing the theory that intensifying caloric intake during the growing phase does not compromise future feedlot performance. Ultrasound marbling scores for MEC-treated cattle were 19° greater than AGR treated cattle (P ≤ 0.05) at the end of the growing phase trial. Nearly the exact same advantage (22°) was observed in the cooler 5 mo later (P = 0.42). Implying MEC metabolically imprinted cattle to favor marbling development. It appears that maximizing dietary caloric density in light-weight calves does not adversely affect the growth curve, while oral dosing of MEC during the growing period may be a precursor for enhanced quality grade.